Consentimento sexual em estudantes universitários: revisão integrativa de literatura - Ibieta, Daniela Paz Tuma (2023)
The prevalence of sexual aggression among college students is far from decreasing, both in Brazil and abroad, being part of university life. Sexual aggression is intrinsically linked to the absence of sexual consent. This study aimed to comprehend the understanding of sexual consent in college students, in the context of national and international scientific literatur, in the last five years. An integrative literature review was performed with a qualitative approach of 18 selected articles, collected in CAPES Platform databases. A content analysis was performed, aided by the AtlasTi software. The results were organized into 3 categories: The relational dynamics on the construction of the understanding of sexual consent in college students; The understanding of sexual consent constituted from theoretical and applied perspectives; Challenges and limitations of the scope of public policies and prevention programs based on sexual consent. In the first category, it was observed that gender-based power dynamics are embedded in sexual consent, defining behaviors and values through traditional scripts. The gender issuesis are fundamental in the explicit and implicit definition of sexual norms and guidelines that are internalized from an early age through sexual scripts in which women are guardians of consent and men are sexual initiators. The second category provides evidence of limitations adopting an affirmative consent standard in sexual assault prevention programming and initiatives in university contexts, as well as further discussions on cultural context, gender dynamics, and negotiation strategies that drive more sexual behavior. safe. The last category attests to an advance in terms of knowledge and awareness on the issue of sexual assault and consent, as a result of the massification of hashtags that allowed the #MeToo movement to grow and gain strength. Finally, the investigated articles showed that university students need better and more sexual education, but much earlier, in adolescence when they start romantically and sexually. Currently, sexual assault prevention programs should focus on more practical and realistic aspects, considering affective and emotional aspects, permeated by the perspective of sexual diversities